A Prothrombotic Score Based on Genetic Polymorphisms of the Hemostatic System Differs in Patients with Ischemic Stroke, Myocardial Infarction, or Peripheral Arterial Occlusive Disease - Herm, Juliane; Hoppe, Berthold; Siegerink, Bob; Nolte, Christian H.; Koscielny, Jürgen; Haeusler, Karl Georg (Frontiers in Cardiovascular Medicine, 2017)
Background: While twin studies indicate a genetic component in arterial thrombosis such as ischaemic stroke, myocardial infarction (MI) or peripheral arterial occlusive disease (PAOD), the clinical relevance of haemostatic polymorphisms in arterial thrombosis is a matter of debate. Methods: We analysed the prevalence of 13 haemostatic polymorphisms (PAI-1, PLAT, F5 (including factor V Leiden and HR2-haplotype), F2, F7, F13A, FGB, TFPI, THBD, MTHFR, ACE and ITGA2) in patients referred to a tertiary referral center. A “prothrombotic score” was calculated by dividing the number of risk-increasing polymorphisms for thrombosis minus the number of risk-lowering polymorphisms (F7 and F13A) by the number of polymorphisms tested. Results: Datasets of 144 patients with prior ischaemic stroke (mean age 44±13 years; 65% female) were compared to 62 patients with MI or PAOD (mean age 54±14 years; 47% female). The prothrombotic score was lower in MI and PAOD patients compared to stroke patients (OR 2.7 [95%CI 1.1-6.2]). Frequencies of individual polymorphisms did not differ between both groups. Conclusion: Patients with MI or PAOD had a lower burden of prothrombotic mutations compared to patients with prior stroke, indicating that a prothrombotic state might play a different role in distinct forms of arterial thrombosis.